EDUKASI KEPADA SISWA SMA TRENSAINS MUHAMMADIYAH SRAGEN DALAM MEMILIH KOSMETIK AMAN BERBASIS FAKTA MEDIS DAN HALAL SESUAI SYARIAT - Satwika Budi Sawitri; Kurniawan; Mahmud Carica Dewi; Otcha Novitasari; Siti Aisyah Rabiah Al Adawiah; Fildzah Aqilah; Qirania Waspha Septiyan; Azka Nabilah; Alyshia Amanda Evriliana; Isma Azzahra; Muhammad Taubah Setiawan (Jurnal Abdi Insani, 2026)
The increasing use of cosmetic products among teenagers requires special attention to the safety and halal of the products used. Lack of understanding of hazardous substances and halal certification can pose a risk to their health and religious beliefs. This community service activity was carried out through interactive counseling to students of SMA Trensains Muhammadiyah Sragen to increase their knowledge and understanding regarding safe and halal cosmetics. Program evaluation was carried out by comparing the results of the pretest and posttest using qualitative analysis of paired test methods and descriptive analysis. The results of the quantitative analysis showed a significant difference in student knowledge based on the pretest and post-test scores of SMA Trensains students in grades 10 and 11. The results of the descriptive analysis showed a significant increase with an increase of 30% from the results of the pretest and posttest scores. This program succeeded in providing more precise insights in choosing cosmetics that are in accordance with the principles of health and halal. These findings also serve as an important basis for implementing a sustainable education program about safe and halal cosmetics among teenagers.